The aftermath of super typhoon Yolanda do Filipinos recover by sharing grief, and support over the internet? - Del Rosario, Angelo Jaiko C.
Super Typhoon Yolanda, also known by its international name Haiyan, was one of the most devastating natural disasters to ever happen to the Philippines. At this point in time, a number of areas hit by the typhoon are still unable to rehabilitate from the damage it brought. Coming from the insight of Filipinos being a tightly knit community, social interaction was a vital part of their recuperating process. These social interactions were not limited to direct face to face interactions but a great deal of these interactions were also done online. Social interactions through social networking sites were prevalent after the occurrence of the super typhoon, especially on Facebook. This study investigated the role of Facebook in the social interactions of two types of college students ? those directly Affected and those Not Affected by the super typhoon. These students were also assessed for symptoms of depression and post-traumatic stress disorder. Thematic analysis was used to determine response patterns in their Facebook activities. Results show that students affected by Yolanda showed depressive and post-traumatic stress disorder symptoms. When asked why they used Facebook after the tragedy, communication and the feeling of relief proved to be the general themes of their responses -- communication to obtain information about the typhoon and read on updates, and relief after reading posts and seeing photos of relief operations. Facebook, being a tool for social interaction for typhoon-affected students, is highlighted in this study.